Simulation of MRAS based speed sensorless estimation techniques for induction machine drives using MATLAB/Simulink - Haron, Ahmad Razani (2006)
This thesis is about the study of the speed sensorless estimation techniques of the induction machine drives. Large variations of techniques are available depending on the estimation requirement. MRAS based speed sensorless estimation is one of the most versatile techniques available due to its good performance and straightforward stability approach. This technique uses two different models (the reference model and the adjustable model) which has made the speed estimation a reliable scheme especially when the motor parameters are poorly known or having large variations. Rotor flux based MRAS (RF-MRAS) and back e.m.f based MRAS (BEMF-MRAS) are two variants of MRAS based speed estimation techniques which differ in terms of quantity used but share almost the same structure realization. These facts give a good platform for comparison. The tracking capability and sensitivity to parameters variation are two key criteria of comparison in assessing the performance of the estimators. Implemented in the direct torque control (DTC) structure and simulated in the MATLAB/Simulink, the results obtained justify the dynamic performance of the RF-MRAS and BEMF-MRAS estimators